Cancer stem cells in human gastrointestinal cancer. Issue 11 (November 2016) - Taniguchi, Hiroaki; Moriya, Chiharu; Igarashi, Hisayoshi; Saitoh, Anri; Yamamoto, Hiroyuki; Adachi, Yasushi; Imai, Kohzoh
Abstract : Cancer stem cells (CSCs) are thought to be responsible for tumor initiation, drug and radiation resistance, invasive growth, metastasis, and tumor relapse, which are the main causes of cancer‐related deaths. Gastrointestinal cancers are the most common malignancies and still the most frequent cause of cancer‐related mortality worldwide. Because gastrointestinal CSCs are also thought to be resistant to conventional therapies, an effective and novel cancer treatment is imperative. The first reported CSCs in a gastrointestinal tumor were found in colorectal cancer in 2007. Subsequently, CSCs were reported in other gastrointestinal cancers, such as esophagus, stomach, liver, and pancreas. Specific phenotypes could be used to distinguish CSCs from non‐CSCs. For example, gastrointestinal CSCs express unique surface markers, exist in a side‐population fraction, show high aldehyde dehydrogenase‐1 activity, form tumorspheres when cultured in non‐adherent conditions, and demonstrate high tumorigenic potential in immunocompromised mice. The signal transduction pathways in gastrointestinal CSCs are similar to those involved in normal embryonic development. Moreover, CSCs are modified by the aberrant expression of several microRNAs. Thus, it is very difficult to target gastrointestinal CSCs. This review focuses on the current research on gastrointestinal CSCs and future strategies to abolish the gastrointestinal CSC phenotype. Abstract : Cancer stem cells (CSCs) are thought to be responsible for tumor initiation, drug and radiation resistance, invasive growth, metastasis, and tumor relapse, which are the main causes of cancer‐related deaths. Therefore, since CSCs are thought to be highly resistant to conventional therapies, an effective and novel cancer treatment would need to eliminate CSCs. This review focuses on current research on gastrointestinal CSCs and future strategies to abolish the CSC phenotype.